THE VIRTUAL LIBRARY PROJECTS IN NIGERIA PRIVATE UNIVERSITIES: THE CASE STUDY OF FOUNTAIN UNIVERSITY LIBRARY, OSOGBO. - Ayo, Salami (Innovare Journal of Education, 2018)
Abstract Fountain University was granted an operational license as a Private University on May 17, 2007 by the Federal Government on the recommendations of the National Universities Commission. Following this achievement, a Fountain Universities Strategic implementation Committee was set up to serve as in loco Councilâ€ to actualize the birth of the University. Fountain university library fit into the word of innovation by encouraging Information and Communication Technology. This paper reported how effort was been made by Fountain university library, Osogbo, the various challenges and the actualization of the virtual library. Among the challenges are as follows: erratic power supply, this is a national problem which regards the choice Fountain university, Osogbo; computer systems are capital intensive and need funds to keep the project going, shortage of managerial and technical expertise in Nigeria must be addressed, there is need for greater commitment within academic circles by librarians to undertake training and retraining in computer literacy, copyright holders have to be contacted and rights obtained.Â And the future plans: there is still much to be done on virtual library in Fountain University Library.